PERANCANGAN ALAT PEMINDAH PERAHU ”MODEL DEREK” UNTUK NELAYAN TRADISIONAL PESISIR PANTAI CURAM - Yudhyadi, IGNK; Suartika, I Made; Zainuri, Achmad; Fajar, M. (Universitas Mataram, 2015)
The steep coastal topography makes the traditional fisherman facing a difficulty for moving boat from/to the sea towards the mainland. With the slope of 2 - 3 meters, it required at least 4 people do the job. This situation is very disturbing and reducing the productivity of the fishermen itself. Therefore, it needs a special equipment or appropriate technology to overcomes the drawback situation. So that, it will improve the efficiency and effectiveness of fishing operations. The method used in this study is an applied research method which the tool is designed based on real phenomena. Moreover, the outcome is the design of boat transfer device that will be used as an additional supplement to the teaching material of design and product development, industrial management, as well as a scientific publications. The design expected can improve the steep coastal fishermen productivity and welfare.